2021
DOI: 10.3390/math9182232
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the Optimization of Financial Structure to the Real Economy: Evidence from China’s Financial System Using TVP-VAR Model

Abstract: How the financial structure promotes the development of real economy has always been a research topic in academia. By analyzing the characteristics of China’s financial system, this paper constructs the Finance Structure Index (FSI) from the perspectives of structural efficiency, financing structure and industry structure, and interprets the trend of the FSI. Based on the quarterly data of China from 2004 to 2020, this paper constructs a time-varying parameter-vector autoregression (TVP-VAR) model to study the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…This overcomes the burden of the often arbitrarily chosen rolling window size that can lead to erratic or flattened parameters and the loss of valuable observations; instead, it is possible to examine the dynamic connectedness at lower frequencies and with limited time series data. Time-varying connectedness can be used to examine correlation effects of one-to-many, many-to-one, and one-to-one among variables (Antonakakis and Gabauer 2017 ; Zhang and Hamori 2021 ; Jebabli et al 2014 ; Liu et al 2021 ) and is introduced here for the purpose of studying the dynamic spillover effect of the carbon price among pilot markets so as to broaden the research of the return dynamic spillover of the pilot markets in China.…”
Section: Introductionmentioning
confidence: 99%
“…This overcomes the burden of the often arbitrarily chosen rolling window size that can lead to erratic or flattened parameters and the loss of valuable observations; instead, it is possible to examine the dynamic connectedness at lower frequencies and with limited time series data. Time-varying connectedness can be used to examine correlation effects of one-to-many, many-to-one, and one-to-one among variables (Antonakakis and Gabauer 2017 ; Zhang and Hamori 2021 ; Jebabli et al 2014 ; Liu et al 2021 ) and is introduced here for the purpose of studying the dynamic spillover effect of the carbon price among pilot markets so as to broaden the research of the return dynamic spillover of the pilot markets in China.…”
Section: Introductionmentioning
confidence: 99%
“…Han and Fu (2020) found that finance has a positive regulatory effect on manufacturing innovation performance. However, Liu et al (2021) study found that the financial structure can promote the scale of the real economy, but the impact on the structure is not obvious. Therefore, it is necessary to further study the impact of finance on the industry.…”
Section: Influencing Factors Of Industrymentioning
confidence: 94%
“…This approach builds on the work of Antonakakis et al (31,32) and Gabauer (33,34) who advances the connectedness approach proposed by Diebold and Yilmaz (35)(36)(37) and overcomes the burden of the often arbitrarily chosen rolling-window-size that can lead to erratic or flattened parameters and loss of valuable observations, being able to examining the dynamic connectedness at lower frequencies and limited time-series data. This method that is mostly applied to research the correlation effects of one-tomany, many-to-one and one-to-one among variables (38)(39)(40)44) is introduced by us to model the dynamic transmission of the COVID-19 epidemic among countries to broaden the research of the dynamic transmission of the global COVID-19 epidemic.…”
Section: Introductionmentioning
confidence: 99%